Nearly cashless: Digital transformation or cultural transmission? - Arina Wischnewsky (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
As economies transition towards digitalization, the shift from cash to noncash alternatives becomes increasingly relevant. While this trend is rapidly advancing in some countries, others continue to rely heavily on cash, underlining the need for central banks to measure and understand cash usage accurately. Numerous studies have attempted to explain the dynamics behind the declining-or, in some instances, paradoxically increasing-utilization of cash in conjunction with the rise of digital payment systems. Yet, the question of what fundamental factors influence cash use and how one might accurately formulate policies for a Central Bank Digital Currency (CBDC), particularly in a diverse European context, remains unanswered. This paper enriches the discourse on digital payment systems and cash usage by exploring the underlying influences on these phenomena. Notably, it provides new crosscountry evidence on cultural and behavioral factors being pivotal in shaping these trends. This study is the first to reveal that (social) trust plays a crucial role in the global shift from cash reliance to digital economy integration, outlining a distinctive non-linear relationship between trust and cash usage.
Keywords: E41; O33; E42; C33; Z1; E7; 330; cash use; digital transformation; culture; national mobile payment system; cashless societies; trust; monetary systems